EMPATI DAN KETERAMPILAN SOSIAL - Zuchdi, Darmiyati (Cakrawala Pendidikan, 2003)
Empathy can only be developed if we understand ourselves.Empathy makes it possible for oneto be involved in a good socialrelationship. There are three methodsto increase empathy, i.e., selfÂintrospection and theuse of an intimate friend for self- reflection,asking for help from professional people, and interacting withsomegroups of people who are participating in emotional sensitivitytraining.Wholeheartedness, doing something without an eye to reward,and empathy are the main human qualitiesto improve socialinteraction. A good communication skill without these three qualitieswillbe worth nothing. So these three aspects should be integrated inone in orderto create a satisfactory relationship.Thereare two polarities in every person; the first one makes onehave a desireto affiliate and the other makes one wish to isolateoneself. A leaderof every institution, including an educationalinstitution, should place thetwo. motives in proportion. Humanorientation, rather than jobor commodity orientation, makes itpossiblefor a leader to see others' perspectives as considerations inreaching a certain goal. This will leadto the development of ahumanistic social interaction